PARENTING AND EMOTIONAL BONDING TO NEPALESE PRESCHOOL CHILDREN: MOTHERS’ PERSPECTIVES FROM DIVERSE SOCIOCULTURAL BACKGROUNDS - Sharma, Prakash (Veredas do Direito, 2026)
Maternal perceptions and practices underpin the development and behavioral sensitivity of preschool children, yet research on day-to-day parenting practices is scarce in Nepal. This study aims to explore the voices of Nepali mothers regarding how they perceive and practice parental care and emotional bonding toward their preschool children in the Rupandehi district of Nepal within diverse socio-cultural context. In-depth interviews were conducted with thirteen mothers of preschool-aged children in Rupandehi district, Nepal. Data were analyzed thematically and identified five key themes: discipline as a strategy for behavioral control, affection and emotional bonding, fulfilling children’s demands as parental care, the importance of obedience and educational behavior, and social interaction with guests and relatives. The study found that mothers adopt diverse parenting techniques. Some rely on fear-based or punitive strategies, while others emphasize emotional bonding, affection and supportive communication. These practices are shaped by cultural norms, social context, ethnicity and level of education. However, most mothers valued obedience, respectful behavior, and appropriate social interaction. This study provides insights for readers how culturally embedded parenting practices influence early childhood development. It suggests that parenting interventions and early childhood education programs should be context-sensitive and promoting positive discipline, emotional bonding, and balanced caregiving practices adaptable across diverse sociocultural settings.